Evaluation of Simulation Based Education Clinical Preparation Program for Unstable Patient Management - Dilek Kitapcioglu; Serpil Yaylaci; Sinem Yildiz Inanici; Mehmet Emin Aksoy; Mehmet Ali Gulpinar (Journal of Systemics, Cybernetics and Informatics, 2021)

(untitled)
In this study, the aim is to evaluate clinical transfer of unstable patient management competencies acquired by learners in simulated environment and evolution of their skills in clinical environment. Performances of 87 intern medical students of Acıbadem Mehmet Ali Aydinlar University that participated in two weeks long simulation based education program were evaluated both in simulated environment and in real clinical environment. Analyzes were performed using the MedCalc Statistical Software version 12.7.7. Observational performance scores of Group A were 18,68±1,70 over 24 point in simulated environment and 19,65±2,87 in first clinical test and 22,12±2,45 in second clinical test. Scores of Group C were 18,9±4,55 in simulated environment 16,36±4,2 in first clinical test, and 23,32±2,44 in second clinical test. Scores of Group D were 14,5±4,04 in simulated environment 19,32±3,76 in first clinical test and 21,87±2,78 in second clinical test. Scores of Group B in simulated environment were 17,68±2,73 but Group B performances could not be evaluated in clinical environment due to pandemic. Simulation-based education is effective for improving the competencies of learners for management of unstable patients.